Investing in the Middle East the political economy of European direct investment in Egypt - Mishrif, Ashraf (International library of economics, 2010)
However, the real challenge is not only to examine the effect of FDI on economic development but also to investigate the most appropriate economic policies that are conducive to increasing levels of FDI. In this book, Ashraf Mishrif addresses this challenge and examines the interplay between external and internal forces to determine whether EU-Egyptian trade agreements have led to any significant improvement in Egypt's investment environment and in the growth levels of European direct investment in the country.